2014
DOI: 10.1088/0004-637x/783/2/131
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the Remnant Clockwise Disk of Young Stars in the Galactic Center

Abstract: We present new kinematic measurements and modeling of a sample of 116 young stars in the central parsec of the Galaxy in order to investigate the properties of the young stellar disk. The measurements were derived from a combination of speckle and laser guide star adaptive optics imaging and integral field spectroscopy from the Keck telescopes. Compared to earlier disk studies, the most important kinematic measurement improvement is in the precision of the accelerations in the plane of the sky, which have a fa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

43
307
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(366 citation statements)
references
References 81 publications
43
307
6
Order By: Relevance
“…The simplest in situ formation scenarios initially produce circular orbits since gas that flows in at low or moderate rates circularizes prior to the onset of star formation (Nayakshin & Cuadra 2005;Alexander et al 2007;Löckmann et al 2009). The observed eccentricity distribution peaks at e=0.3 Yelda et al 2013). Scenarios invoking more rapid gas inflow, such as the infall of a single molecular cloud or the collision of two molecular clouds, could produce disk stars with large initial eccentricities and have the added bonus of producing a large population of young stars off the disk (Bonnell & Rice 2008;Wardle & Yusef-Zadeh 2008;Hobbs & Nayakshin 2009;Mapelli et al 2012), similar to what has been observed (Paumard et al 2006;Bartko et al 2009;Lu et al 2009;Yelda et al 2013).…”
Section: The Young Nuclear Clustersupporting
confidence: 77%
See 2 more Smart Citations
“…The simplest in situ formation scenarios initially produce circular orbits since gas that flows in at low or moderate rates circularizes prior to the onset of star formation (Nayakshin & Cuadra 2005;Alexander et al 2007;Löckmann et al 2009). The observed eccentricity distribution peaks at e=0.3 Yelda et al 2013). Scenarios invoking more rapid gas inflow, such as the infall of a single molecular cloud or the collision of two molecular clouds, could produce disk stars with large initial eccentricities and have the added bonus of producing a large population of young stars off the disk (Bonnell & Rice 2008;Wardle & Yusef-Zadeh 2008;Hobbs & Nayakshin 2009;Mapelli et al 2012), similar to what has been observed (Paumard et al 2006;Bartko et al 2009;Lu et al 2009;Yelda et al 2013).…”
Section: The Young Nuclear Clustersupporting
confidence: 77%
“…The observed eccentricity distribution peaks at e=0.3 Yelda et al 2013). Scenarios invoking more rapid gas inflow, such as the infall of a single molecular cloud or the collision of two molecular clouds, could produce disk stars with large initial eccentricities and have the added bonus of producing a large population of young stars off the disk (Bonnell & Rice 2008;Wardle & Yusef-Zadeh 2008;Hobbs & Nayakshin 2009;Mapelli et al 2012), similar to what has been observed (Paumard et al 2006;Bartko et al 2009;Lu et al 2009;Yelda et al 2013). However, the evolution of an initially circular disk over 4-6 Myr depends on the initial mass function (IMF) of the stars and it is possible to evolve to today's observed distribution for moderately top-heavy IMFs .…”
Section: The Young Nuclear Clustermentioning
confidence: 87%
See 1 more Smart Citation
“…The trajectories of young stars are known from proper motion measurements in the near-IR. To see if these stars have radio continuum counterparts, their positions at the epoch of our 34 GHz observation on 2014 March 9 (2014.19) have been calculated based on proper motions and orbital accelerations have been derived from near-IR observations (Lu et al 2009;Gillessen et al 2009;Yelda et al 2014). Tables 2 and 3 give the positions of the S-cluster and their corresponding positional uncertainties at the epoch of 2014.19 and from two different catalogs (Gillessen et al 2006;Lu et al 2009).…”
Section: Radio Emission From the S Clustermentioning
confidence: 99%
“…The images were centered near the position of Sgr A* and span 10 arcseconds (∼ 0.4 pc at R 0 ≈ 8.0 kpc), and were taken over 37 nights between July 2004 and May 2016 (observation setup used here is further detailed by Ghez et al 2008 andYelda et al 2014). …”
mentioning
confidence: 99%